Imperial overstretch? The United States and the rising costs of the war on terrorism - Jens van Scherpenberg (Stiftung Wissenschaft und Politik (SWP), 2003)
The division and unification of Germany as part of the rise and fall of the Soviet empire.Why was Germany divided after the Second World War? Why was the division of Germany maintained for almost half a century? Why did the Soviet Union accept German unification? And why did it consent to unified Germany as a full member in the Atlantic Alliance?The answers to these questions are placed in the context of the rise, decline and collapse of the Soviet empire. The division of Germany was not part of Stalin's post-war plans in Europe, it is argued, but followed an imperial logic that was reinforced by Soviet ideology. The party leaderships from Stalin to Chernenko contended with this reality but refused to provide effective remedies. The cure Gorbachev attempted was to modernize and humanize the empire, but his approach failed. Instead, he set in motion processes over which he lost control. German unification was one of the unintended consequences of an uncontrollable dynamics. Similarly, unified Germany's membership in NATO contradicted Gorbachev's preferences. He consented to it because of Western firmness on the issue and the lack of a better alternative.(SWP Comments / SWP)
Keywords: 320